Long-term effects of combined B-cell immunomodulation with rituximab and belimumab in severe, refractory systemic lupus erythematosus: 2-year results - Kraaij, Tineke (Nephrol Dial Transplant, 2020)
BACKGROUND: Anti-CD20 B-cell depletion has not shown superior efficacy to standard immunosuppression in patients with systemic lupus erythematosus (SLE). Besides trial design, potential explanations are incomplete B-cell depletion in relation to substantial surges in B-cell-activating factor (BAFF). To improve B-cell targeting strategies, we conducted the first study in SLE patients aimed at investigating immunological effects and feasibility of combining rituximab (RTX; anti-CD20) and belimumab (BLM; anti-BAFF). METHODS: Reported is the long-term follow-up of a Phase 2 proof-of-concept study in 15 patients with SLE including 12 (80%) with lupus nephritis (LN). RESULTS: In 10/15 (67%) patients, a clinical response was observed by achievement of lupus low disease activity state, of which 8 (53%) continued treatment (BLM + ≤7.5 mg prednisolone) for the complete 2 years of follow-up. Five patients (33%) were referred to as ‘non-responders’ due to persistent LN, major flare or repetitive minor flares. Out of 12 LN patients, 9 (75%) showed a renal response including 8 (67%) complete renal responders. All anti-dsDNA(+) patients converted to negative, and both anti-C1q and extractable nuclear antigen autoantibodies showed significant reductions. CD19(+) B cells showed a median decrease from baseline of 97% at 24 weeks, with a persistent reduction of 84% up to 104 weeks. When comparing responders with non-responders, CD20(+) B cells were depleted significantly less in non-responders and double-negative (DN) B cells repopulated significantly earlier. CONCLUSIONS: Combined B-cell targeted therapy with RTX and BLM prevented full B-cell repopulation including DN B cells, with concomitant specific reduction of SLE-relevant autoantibodies. The observed immunological and clinical benefits in a therapy-refractory SLE population prompt further studies on RTX + BLM.